(untitled) (International Journal of Medicine and Medical Sciences, 2019)
Ethanol extract of dietary vegetable, Gongronema latifolium, was evaluated for anti-ulcer activity. The extract was obtained from air-dried, pulverized leaves of the plant following its maceration in ethanol, filteration with Whatman No. 1 filter paper and drying at 110°C. Fractionation of the dry crude ethanol extract was stepwisely carried out in with n-hexane, chloroform and ethylacetate, respectively, and their residual ethanol extract washed several times in ethanol. The four fractions were dried at low temperature and stored for use. The anti-ulcer activity of the crude extract was tested on indomethacin-induced and acid/ethanol-induced models of ulcer induction in rats. The activities of the fraction of the crude ethanol extract with respect, to reduction of ulcer index was evaluated only on indomethacin-induced ulcer model. The crude ethanol extract significantly (p<0.05) inhibited ulceration dose - dependently in the two ulcer models. This inhibition was higher in acid/ethanol model than in the indomethacin-induced ulcer model. The sub-fractions from the crude extract also inhibited ulcer with the chloroform fraction exhibiting the highest ulcer protection.